ErbB- and MUC1-targeted CAR-T cell immunotherapy of oral squamous cell carcinoma - Summers, Saffron E.; Salih, Vehid; Foey, Andrew D. (Frontiers in Dental Medicine, 2023)
Chimeric antigen receptor T (CAR-T) cell therapy has shown great success in treating B cell malignancies; however, there are many challenges that limit their therapeutic efficacy in solid tumours. Immunotherapy of head and neck squamous cell carcinoma (HNSCC), and, in particular, oral squamous cell carcinoma (OSCC), presents a unique set of challenges including lack of consistently expressed tumour associated antigens (TAAs) and the immunosuppressive tumour microenvironment (TME). Currently, there are few clinical trials investigating the use of CAR-T cells in HNSCC/OSCC; however, results from trials investigating similar solid tumours, such as breast cancer, can be adopted to help evaluate the use of CAR-T in this cancer. In this review, the process of CAR-T cell engineering and different generations of these cells will be summarised, highlighting their potential use in treating HNSCC through targeting ErbB and MUC1; TAAs highly expressed by this solid tumour. Potential strategies including combination therapy, utilising both TAA-targeting CAR-Ts and immune checkpoint inhibitors, such as PD-L1, have been discussed, in an attempt to develop synergistic anti-tumour responses. In addition to this, the use of dual-targeting CAR-T cells, synthetic NOTCH (synNOTCH) receptors and alternative non-tumour targets of the TME have been reviewed. Such combination therapies have been shown to help limit solid tumour progression and enhance both the safety and efficacy of CAR-T cell immunotherapy, which may be adopted for the treatment and management of OSCC.